First PCR confirmed anthrax outbreaks in Ethiopia–Amhara region, Ethiopia 2018–2019 - Wassie, B.A.; Fantaw, S.; Mekonene, Y.; Teshale, A.M.; Yitagesu, Y.; Tsige, E.; Getahun, D.; Tasew, G.; Abichu, G.; Moges, B.; Abate, E.; Abayneh, T.; et al. (2022)
Background Anthrax is a disease that affects humans and animals. In Ethiopia, anthrax is a reportable disease and assumed to be endemic, although laboratory confirmation has not been routinely performed until recently. We describe the findings from the investigation of two outbreaks in Amhara region.